Canine adipose tissue-derived MSCs engineered with mRNA to overexpress TSG-6 and enhance the anti-inflammatory effects in canine macrophages - Yun, Ga-Hee; Park, Su-Min; Lim, Ga-Hyun; Seo, Kyoung-Won; Youn, Hwa-Young (Frontiers in Veterinary Science, 2023)
Background Mesenchymal stem cells (MSCs) are useful agents in the treatment of various inflammatory diseases. The immunomodulatory effects of MSCs are largely related to their secretory properties. mRNA engineering emerged as a safe alternative to enhance the secretory function of MSCs. Optimization of the untranslated region (UTR) sequence is important for enhancing the translational efficiency of exogenous mRNAs. However, research on the optimization of UTR in canine MSCs has not yet been conducted. Objectives We aimed to identify the UTR sequence related to the expression efficiency of in vitro transcription (IVT) mRNA in canine MSCs and investigate whether mRNA-engineered MSCs that overexpress TSG-6 exhibit enhanced anti-inflammatory effects. Methods Canine adipose tissue-derived (cAT)-MSCs were transfected with green fluorescence protein (GFP) mRNA with three different UTRs: canine hemoglobin subunit alpha-like 1 (HBA1), HBA2, and hemoglobin subunit beta-like (HBB). The translation efficacy of each mRNA was evaluated using relative fluorescence. TSG-6 mRNA was produced with the UTR optimized according to relative fluorescence results. cAT-MSCs were transfected with TSG-6 mRNA (MSCTSG-6), and TSG-6 expression was analyzed using real-time quantitative PCR, ELISA, and western blotting. To evaluate the anti-inflammatory effects of MSCsTSG-6, DH82 cells were co-cultured with MSCsTSG-6 or treated with dexamethasone, and changes in the expression of inflammatory cytokines were analyzed using qPCR. Results The highest fluorescence level was observed in the HBA1 UTR at 24 h post-transfection. TSG-6 mRNA transfection yielded high levels of TSG-6 in the cAT-MSCs. In DH82 cells co-cultured with MSCsTSG-6, the expression of inflammatory cytokines decreased compared to that in co-culturing with naïve MSCs and dexamethasone treatment. Conclusions Optimization of the HBA1 UTR improved the translation efficiency of IVT mRNA in canine MSCs. cAT-MSCs engineered with TSG-6 mRNA effectively enhanced the anti-inflammatory effects of the MSCs when co-cultured with LPS-activated DH82 cells.